Biochar from waste biomass, its fundamentals, engineering aspects, and potential applications: an overview - Kannan, N.; Asharp, T.; Jeganathan, Y. (International Water Association, 2024)
Environmental pollution control in the growing world is a challenging task for all the countries in order to keep the environmental sustainability. Biochar, a processed carbon material, draws a significant attention in the field of environmental remediation, as of its active functional groups that help remove environmental pollutants to a level insignificant to cause hazardous effects. As such, there is an increasing interest developed to promote highly productive biochar for exploring environmental engineering aspects. There is limited comprehensive literature available for understanding biochar science and its potential applications under an umbrella. This review was set to fill this knowledge gap by discussing key points related to biochar, its novel engineering aspects and potential environmental applications. Therefore, this overview tends to summarize and discuss biochar, its fundamentals, engineering aspects commonly used modifications and the potential applications of biochar in water treatment with an intention of addressing the importance of biochar for environmental remediation process. This overview will be useful for researchers, policy-makers and stakeholders to plan and review relevant scientific works in order to produce customized biochar for future environmental applications.
Keywords: Engineered biochar; Environmental remediation; Hydrochar; Pollution control; Pyrolysis